A cidade e os afetos: a representação de resíduos coloniais e escravistas no filme Praça Paris (2017) - Fazzini, Luca (Brasiliana: Journal for Brazilian Studies, 2019)
This article analysis the film Praça Paris (2017), directed by Lúcia Murat, showing how this work points to the residues of colonialism and slavery in the urban contemporary city of Rio de Janeiro. By establishing links between characters and symbolic spaces in the city of Rio, the Murat’s film proposes a reading of contemporary racisms. From a diachronic reading of the interventions performed by the public power in the carioca metropolis, the article highlights the relevance of political affects both in the construction of urban space and in the relations between alterities, shaped at the structural level by the practices of racism.